Synergism between the Synthetic Antibacterial and Antibiofilm Peptide (SAAP)-148 and Halicin - Miriam E. van Gent; Tanny J. K. van der Reijden; Patrick R. Lennard; Adriëtte W. de Visser; Bep Schonkeren-Ravensbergen; Natasja Dolezal; Robert A. Cordfunke; Jan Wouter Drijfhout; Peter H. Nibbering (MDPI AG, 2022)
Recently, using a deep learning approach, the novel antibiotic halicin was discovered. We compared the antibacterial activities of two novel bactericidal antimicrobial agents, i.e., the synthetic antibacterial and antibiofilm peptide (SAAP)-148 with this antibiotic halicin. Results revealed that SAAP-148 was more effective than halicin in killing planktonic bacteria of antimicrobial-resistant (AMR) Escherichia coli, Acinetobacter baumannii and Staphylococcus aureus, especially in biologically relevant media, such as plasma and urine, and in 3D human infection models. Surprisingly, SAAP-148 and halicin were equally effective against these bacteria residing in immature and mature biofilms. As their modes of action differ, potential favorable interactions between SAAP-148 and halicin were investigated. For some specific strains of AMR E. coli and S. aureus synergism between these agents was observed, whereas for other strains, additive interactions were noted. These favorable interactions were confirmed for AMR E. coli in a 3D human bladder infection model and AMR S. aureus in a 3D human epidermal infection model. Together, combinations of these two novel antimicrobial agents hold promise as an innovative treatment for infections not effectively treatable with current antibiotics.